Batas-batas Keabsahan Berkontrak - Peter Mahmud Marzuki (Yuridika, 2019)
Freedom of contract serves to be a central principle in contract law. The principle, however, is without limitation. To avoid manipulation of the principle, the principles of aequitas prastationis and justrum pretium are added to it. Read More